Immunogenic proteins of Orientia tsutsugamushi and implications for scrub typhus intervention: A narrative review - Shakshi Shah; Ankita Sharma; Alka Rana; Rakesh Kumar; Amit Kumar Sharma; Sunil Kumar; Dixit Sharma (Asian Pacific Journal of Tropical Medicine)
Scrub typhus is an acute undifferentiated febrile infectious disease transmitted by a chigger (genus Leptotrombidium) bite carrying Orientia (O.) tsutsugamushi, affecting millions of people annually while more than one billion people are susceptible. Endemic areas are expanding to Africa, Europe, Middle East, and South America which is concerning, as despite best efforts, there is no vaccine to combat the bacteria. There are now three species of Orientia and over 20 strains of O. tsutsugamushi. The past attempts to develop a vaccine have been ineffective as they confer homologous strain-specific immunity. Various immunogenic proteins of O. tsutsugamushi have been identified that interact with the extracellular matrix (fibronectin) or vMLL5 receptor and modify the cytoskeleton of non-phagocytic host cells, which aids in host cell adhesion and invasion. These highly conserved proteins involve type specific antigen 56 (TSA56), 47 kDa, OmpA, and autotransporter proteins (ScaA, ScaB and ScaC). TSA56 is the most immunogenic and contains four types of hypervariable regions. Out of all autotransporter proteins, ScaA provides the homologous strains specific immunity and when coupled with TSA56 it shows better protective immunity against heterologous strains. The review provides detailed insight into the potential immunogenic proteins of Orientia which can be utilized to develop the vaccine. Furthermore, studies focused on highly antigenic proteins will provide more insight into their roles in developing therapeutics and easy-to-handle rapid diagnostic kits.